Appraisal of pollution, ecological and health risks assessment of trace metals in soils of Logbadjeck quarrying area, Nyong Series, Cameroon - Anicet Feudjio Tiabou; Guy Amie Atabe Atabe; Cyrille Sigue; Lemnyuy Prosper Yiika; Fatemeh Kachoueiyan; Nkeng Enstein Forchenallah (Journal of Trace Elements and Minerals)
Background: Assessing toxic metals in agricultural soils or farmlands is a worldwide concern for maintaining ecosystem health, especially in developing countries such as Cameroon. Therefore, this study examines the contamination levels and the ecological and health risks of trace metals in the soils of the Logbadjeck quarrying area. Methods: Soil samples from the Logbadjeck quarrying area were examined using Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). Results and discussion: The findings of this research show that trace metals in soils examined significantly exceeded the permissible limit. Correlation matrix and principal component analysis suggest similar provenance of trace metals. A low to moderate level of contamination was found using the geo-accumulation index, ecological risk index, and contamination factor. Logbadjeck soils had minimal pollution levels, as indicated by most stations with pollution load index values < 1 and Nemerow integrated pollution index values of 1–2. The ecological and toxic risk index shows negligible ecological risk and no toxic risk levels of trace metals. The health risk assessment's findings showed that while accidental ingestion and skin contact with trace metals in soils exposed recreational receptors to carcinogenic and non-carcinogenic risks, it was necessary to implement policies and undertake remediation to control the elevated carcinogenic risks of Cr, Ni, and Pb in soil. This study's data offers profound insights into our knowledge of environmental contaminants and their potentially harmful impacts in the study area. Conclusion: The soils of the Logbadjeck quarrying area are in the low to moderate contamination category due to geogenic influences and anthropogenic practices. It is recommended that ongoing soil and agricultural products be monitored to avoid trace metal concentrations from anthropogenic practices in the food chain rising above permissible bounds and safeguard the health of humans and animals in the research region.